Cataract surgery in small pupils - Boris Malyugin (Indian Journal of Ophthalmology, 2017)
This paper presents the review of historical aspects and the current state-of-the-art in various pupil dilatation methods to be used in cataract surgery. The surgical algorithm in managing small pupil cases should include topical and intraocular mydriatics, appropriately selected viscosurgical device and mechanical dilatation with instruments, iris hooks, and/or pupil expanders.